Imobilização da enzima β-galactosidase de Kluyveromyces fragilis em agarose e quitosana utilizando diferentes protocolos de ativação - Vieira, Danielle Cristina (Universidade Federal de São Carlos, 2009)
The objective of this work was stabilize and immobilize β-galactosidase from activated agarose and chitosan supports. Initially, it was evaluated the buffer type, ionic strength and bivalent ions Mn2+ and Mg2+ on the hydrolytic activity of the enzyme using as substrates lactose and o-NPG (o-nitrophenyl galactopyranoside). Then the enzyme was covalently immobilized on glyoxyl-agarose, epoxy-chitosan-alginate and chitosan activated with glutaraldehyde, encapsulation in agarose and chitosan and ionic adsorption on MANAE-agarose. After immobilization, different strategies were used to stabilize the derivative such as crosslinking with glutaraldehyde and polyaldehyde dextran for the enzyme immobilized by ionic adsorption and reduction with sodium borohydride (NaBH4) for the enzyme covalently immobilized. For the derivative with maximum catalytic activity obtained, we estimated the kinetic and biochemical parameters as well as thermal stability at different temperatures and storage, operational stability, effect of inhibition by galactose and lactose yield. In the lactose hydrolysis, the best conditions were evaluated at 45°C in 100 mM potassium phosphate buffer pH 7.0 and addition of 2 mM MgCl2 and 0.1 mM MnCl2 (6786.5 U/mL of crude extract) and in the hydrolysis of synthetic substrate, o-NPG, the conditions for maximum catalytic activity was buffer sodium phosphate pH 7.0 50 mM with 2 mM MgCl2 at 25°C (4466.1 U/mL of crude extract). The enzyme immobilization on glyoxyl-agarose at pH 10.05 inactivated the enzyme. At pH 7.0, the enzyme was not immobilized. Similar behavior was observed for the enzyme immobilized on epoxy-chitosan-alginate. The ionic adsorption of the enzyme on MANAE-agarose allowed obtaining derivatives with high catalytic activity and immobilization yield around 100%. Neverthelless the crosslinking of the immobilized enzyme using polyaldehyde dextran and glutaraldehyde reduced drastically the hydrolytic activity of the derivatives by distortion of the enzyme structure. Besides the thermal stability of these derivatives at 10°C showed a similar behavior to the free enzyme. In order to obtain a derivative with high thermal stability on catalytic activity, the covalent immobilization on coagulated chitosan by different solutions and temperature. The derivative that provided higher catalytic activity was coagulated in a solution of 0.5 M KOH at 50°C and activated with glutaraldehyde 0.8% (v/v), with immobilization yield and recovered activity of 100%. An assay of looding of the support showed that 247,0 mg protein/ g gel was the maximum load. However diffusional limitation was verified even at 25 mg/g of gel. The immobilization process did not change the biochemical properties of the enzyme (optimum temperature and pH). In the storage stability at 10 ° C, the derivative covalently immobilized lost only 20% of initial activity after 90 days. The enzyme immobilized on chitosan was 3-5 fold more stable than the soluble enzyme at 20 and 40°C. The operational stability in 4 cycles showed a loss of 17% of hydrolytic activity after 4 cycles. Another important fact was the smallest effect of inhibition by galactose compared to soluble enzyme, even at high concentrations (5 g/L). In the hydrolysis of lactose the conversion was 70 % using insoluble and immobilized enzymes. We can conclude that the β-galactosidase immobilized on chitosan activated with glutaraldehyde showed good properties, because it allows the development of continuous processes, facility of downstream process (product purification), avoiding contamination of the product by the biocatalyst. This advantage is very important specially for food industry.
Keywords: Imobilização; Quitosana; Agarose; Enzimas; Lactose; Immobilization; Agarose and chitosan; ENGENHARIAS::ENGENHARIA QUIMICA